Study on stability of underlying room and pillar old goaf in close coal seam and mining of the upper coal seam - Liu, Hongtao; Hao, Cheng; Wang, Zhiwen; Li, Chong; Guo, Linfeng; Liang, Jialu; Wang, Haozhu (Frontiers in Earth Science, 2023)
Possible issues during mining of the upper coal seam in old goaf of nearby coal seams, including step subsidence, gas overflow in goaf, and roadway around rock fragmentation. Using the Hanjiawa Coal Mine’s upper coal seam mining, which takes place 28 m above the working face of the lower coal seam, as the research’s focal point. The paper focuses on the self-stability of the coal pillar in the old goaf, the failure form of the upper coal seam mining floor, the roof caving rule of the old goaf in the lower coal seam mining of the upper coal seam, and the bearing capacity of the interlayer rock strata using the pillar goaf stability evaluation system, field geological borehole electrical logging and borehole peeping, finite element difference numerical calculation, and other methods. The conclusion that the old goaf’s coal pillar can be completely stable and that the interlayer rock strata can bear the stress of upper coal seam mining is reached. The results show that the failure depth of the coal pillar in the lower coal seam old goaf is 1–3 m, the maximum failure depth accounting for 15% of the width of the coal pillar, and the failure depth of the roof in the old goaf is 0–3 m; After the mining of the upper coal seam, the floor above the coal pillar of the lower coal seam is plastic failure, and the failure depth is 1–10 m, and the failure depth of the roof of the old goaf of the lower coal seam is 3–15 m, which is 4 times greater than that before the mining. The maximum failure depth of the interlayer rock strata is 22 m, accounting for 78.6% of the rock strata spacing. The interlayer rock strata can bear the mining disturbance of the upper coal seam. The plastic zone of the floor of the upper coal seam is not connected with the plastic zone of the roof of the lower coal seam.